Anti-fouling porcelain glaze and preparation method thereof
By microwaved and acidic reagent treatment of granite blocks, combined with the use of carbon black and mixed base materials, a glaze of anti-fouling porcelain products was prepared, which solved the problem of stains in traditional ceramic products, and achieved efficient crushing and improving the stain resistance and wear resistance of glaze.
Patent Information
- Application Number
- CN202510416246.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-06-13
AI Technical Summary
Traditional ceramic products are prone to stains after use, mainly due to small pits, pinholes and tiny cracks on the surface, resulting in stain absorption.
A glaze of anti-fouling porcelain products is adopted. The preparation method includes microwaveing the granite block, heating and adding carbon black to insulate it, cooling and adding acidic reagents and crushing, and then adding mixed base material, deionized water and aluminum balls for ball milling and sieving to obtain glaze of anti-fouling porcelain products.
It improves the crushing efficiency of granite blocks, extends the service life of crushing equipment, reduces energy consumption and cost, and improves the stain resistance and wear resistance of glaze.
Smart Images

Figure BDA0005344022000000081 
Figure BDA0005344022000000091 
Figure BDA0005344022000000092
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of glazes, and relates to an anti-staining glaze for porcelain products and a preparation method thereof. Background Art
[0002] There are various types of ceramic products, including ceramic tiles, ceramic tableware, ceramic sanitary wares, etc. They are necessities for a good life. While people enjoy the convenience they bring, there are also widespread problems that affect the aesthetics. For traditional ceramic products, especially sanitary ceramic products, after being used for a period of time, a layer of stains is likely to form on the surface of the products. For example, urine, scale, soap foam, fatty acids, etc. are likely to accumulate in the uneven places on the product surface or enter the micropores under the action of various physical or chemical forces such as van der Waals force, capillary force, and hydrogen bond, resulting in the pollution of sanitary ceramic products. The main reason for the stain absorption phenomenon of sanitary ceramic products is the defects such as small pits, small pinholes, and minute cracks existing on the surface of the products.
[0003] Granite mainly consists of quartz, feldspar, and mica, among which the feldspar content is 40% - 60%, and the quartz content is 20% - 40%. Its color depends on the types and amounts of the components contained. Granite is a rock with a fully crystalline structure. High-quality granite has fine and uniform grains, a compact structure, a large amount of quartz, and bright feldspar luster. At the same time, it is hard in texture, acid and alkali resistant, and has good weather resistance. It is a very good raw material for preparing anti-staining glazes. However, the internal binding force of granite is high, the structure is stable and not easily damaged. When preparing granite powder, the loss of the pulverizing equipment is relatively large, which affects its application in the ceramic field. Summary of the Invention
[0004] The purpose of the present invention is to provide an anti-staining glaze for porcelain products and a preparation method thereof. The granite block pulverizing process has the characteristics of high pulverizing efficiency, and the anti-staining porcelain products obtained by firing with the glaze of the present invention have good anti-staining ability.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] An anti-staining glaze for porcelain products, characterized in that the preparation method of the anti-staining glaze for porcelain products comprises the following steps:
[0007] 1) Microwave-treat the granite blocks and then heat them. Add carbon black and keep them warm. Cool to room temperature, add an acidic reagent and pulverize to obtain a mixed material;
[0008] 2) Add a mixed base material, deionized water, and aluminum balls to the mixed material for ball milling. After sieving, an anti-staining glaze for porcelain products is obtained.
[0009] As a preferred technical solution of the present invention, the granite blocks added in the present invention mainly consist of quartz, feldspar and mica. Quartz is usually ground into fine powder and added to ceramic materials as a filler. The quartz powder can make the internal structure of the glaze layer compact and the surface smooth and flat, which helps to prevent dirt deposition and improve the stain resistance and wear resistance of the glaze layer surface; the feldspar of the granite block can also enhance the adhesion and hardness of the glaze layer and other properties, thereby improving the stain resistance of the ceramic glaze.
[0010] As a preferred technical solution of the present invention, the conditions for microwave treatment are a microwave power of 6.0 - 6.5 kW and a microwave treatment time of 5 - 6 min.
[0011] As a preferred technical solution of the present invention, the conditions for heating are heating to 1400 - 1600 °C.
[0012] As a preferred technical solution of the present invention, the mass ratio of the granite blocks to carbon black is 5:0.28 - 0.32.
[0013] As a preferred technical solution of the present invention, the conditions for heat preservation are at a pressure of 0.01 - 0.1 Pa and heat preservation for 30 - 45 min.
[0014] As a preferred technical solution of the present invention, the mass ratio of the granite blocks to the acidic reagent is 30:1.3 - 1.5; the acidic reagent is a citric acid aqueous solution with a concentration of 6.5 - 8 mol / L.
[0015] As a preferred technical solution of the present invention, the mass ratio of the mixed material to the mixed base material is 1:0.8 - 1.0.
[0016] As a preferred technical solution of the present invention, the mixed base material is composed of potassium feldspar, sodium feldspar, quartz, zinc oxide, calcite, dolomite, wollastonite, calcined alumina powder, Hunan kaolin, zirconium silicate, 809 frit, burnt talc, terbium oxide, dysprosium oxide, barium carbonate and sodium carboxymethyl cellulose in a mass ratio of 16 - 18:7 - 9:28.5 - 30.5:3 - 5:7 - 9:2.5 - 5:12 - 14:3 - 5:5 - 8:9 - 11:2 - 5:2.5 - 5:0.1 - 0.2:0.08 - 0.10:0.5 - 2.5:0.2 - 0.3 mixed.
[0017] As a preferred technical solution of the present invention, the weight ratio of deionized water: mixed material and mixed base material: aluminum balls is 3:2:1.
[0018] As a preferred technical solution of the present invention, the sieving is through a 130 - mesh sieve.
[0019] As a preferred technical solution of the present invention, the granite blocks are taken from the cut-off scraps of granite, and are composed of SiO 2 、Al 2 O 3 、Fe 2 O 3 、CaO, MgO, K 2 0、Na 2 O and TiO 2 in a mass ratio of 66.46:14.00:6.67:0.98:4.12:2.91:4.01:0.85.
[0020] Advantages of the present invention:
[0021] (1) In the present invention, the granite blocks contain iron mica and iron serpentine which contain iron elements, resulting in their abnormal sensitivity to microwave irradiation. By microwave irradiation treatment, the internal temperature of the granite blocks rises rapidly, the mechanical properties of the granite blocks are significantly weakened, and the cracks generated after the microwave irradiation treatment incorporate carbon black. The carbon black penetrates into the interior of the granite blocks, increasing the total carbon content of the granite blocks. Combined with the addition of an acidic reagent, the strength of the granite blocks can be further reduced to achieve the effect of being easily crushed, greatly improving the crushing efficiency of the granite blocks using the solution of the present invention, effectively prolonging the service life of the crushing equipment, reducing energy consumption, saving costs, and meeting the requirements of environmental protection and energy conservation.
[0022] (2) Zinc oxide can control the color and luster of the glaze, make the fired glaze surface smooth, flat and dense, avoid the generation of microcracks on the glaze surface, improve the stain resistance and thermal stability of the glaze, and at the same time improve the hardness and durability of the glaze layer. It can improve the bonding property between the body and the glaze, enhance the stability of the glaze, increase the tensile strength of the glaze, change the melting temperature and surface tension of the glaze, contribute to the formation of the intermediate layer, and secondly, it can reduce the microcracks on the glaze surface, making the glaze surface more dense and at the same time contributing to the improvement of wear resistance.
[0023] (3) Alumina acts as a rheological agent in the glaze, can improve the fluidity of the glaze liquid, make the glaze layer uniform, reduce the waiting time, improve the bonding property of the glaze, enhance the stability of the glaze surface, increase the hardness and tensile strength of the glaze surface, and resist the damage of needle-like substances. Alumina contributes to the formation of the intermediate layer by changing the melting temperature and surface tension of the glaze, and secondly, it can reduce the microcracks on the glaze surface, making the glaze surface more dense and at the same time contributing to the improvement of wear resistance.
[0024] (4) By introducing a certain amount of barium carbonate, the present invention can increase the density and viscosity of the glaze liquid, making the glaze more easily adhere to the ceramic surface and reducing the precipitation of suspended substances. Barium carbonate can also reduce the bubbles appearing during the formation of the glaze layer, thereby achieving a smoother and more uniform surface. By utilizing the fact that barium oxide has a stronger influence on the fluidity of the molten glaze than calcium oxide, as a network modifier, it further improves the fluidity of the glaze melt at high temperatures, making the fired glaze surface smooth and dense, and avoiding the appearance of small pinholes and microcracks.
[0025] (5) By adding high-melting-point terbium oxide and dysprosium oxide, the present invention can increase the melting temperature of the glaze and reduce the viscosity of the glaze, promoting the gradual discharge of gas from the glaze, thereby obtaining a relatively compact glaze layer. Moreover, the grain boundaries and grains of the glaze surface will also be denser, significantly reducing the appearance of glaze surface defects such as pinholes and cracks, and thus improving the quality of the glaze surface.
[0026] (6) By adding an acidic reagent as a grinding aid to reduce the wear between powders, and while the addition of the acidic reagent can effectively reduce the strength of granite blocks, it is conducive to the uniform dispersion of metal oxides in the grinding system, further improving the quality of the glaze surface. Specific Embodiments
[0027] To further elaborate on the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following, in conjunction with embodiments, details the specific embodiments, structures, features, and their effects of the present invention as follows.
[0028] The compositions of the ceramic tile bodies used in all the embodiments and comparative examples of the present invention are as follows:
[0029] The ceramic tile body includes the following components by weight parts:
[0030] 26.6 parts of kaolin, 12.7 parts of feldspar, 12.5 parts of calcined talc, 2.2 parts of diatomaceous earth, and 23.6 parts of quartz.
[0031] Example 1
[0032] A method for preparing an anti-fouling porcelain product glaze includes the following steps:
[0033] 1) After microwave treating granite blocks, heat them, add carbon black and then keep them warm, cool to room temperature, add an acidic reagent and pulverize to obtain a mixed material; wherein, the conditions of the microwave treatment are a microwave power of 6.5 kW and a microwave treatment time of 6 min; the conditions of the heating are heating to 1600 °C; the mass ratio of the granite blocks to carbon black is 5:0.28; the conditions of the heat preservation are a pressure of 0.01 Pa and a heat preservation time of 30 min; the mass ratio of the granite blocks to the acidic reagent is 30:1.3; the acidic reagent is a 6.5 mol / L aqueous citric acid solution;
[0034] 2) Add a mixing base material, deionized water, and aluminum balls to the mixed materials and conduct ball milling. After sieving, an anti-fouling porcelain glaze is obtained. Among them, the mass ratio of the mixed materials to the mixing base material is 1:0.8; the mixing base material is composed of potassium feldspar, sodium feldspar, quartz, zinc oxide, calcite, dolomite, wollastonite, calcined alumina powder, Hunan kaolin, zirconium silicate, 809 frit, calcined talc, terbium oxide, dysprosium oxide, barium carbonate, and sodium carboxymethyl cellulose in a mass ratio of 16:7:28.5:3:7:2.5:12:3:5:9:2:2.5:0.1:0.08:0.5:0.2; the weight ratio of the deionized water: the mixed materials and the mixing base material: the aluminum balls is 3:2:1; the sieving is through a 130-mesh sieve.
[0035] The granite blocks are taken from the cut-off corners of granite and consist of SiO 2 , Al 2 O 3 , Fe 2 O 3 , CaO, MgO, K 2 0, Na 2 O, and TiO 2 composed in a mass ratio of 66.46:14.00:6.67:0.98:4.12:2.91:4.01:0.85.
[0036] Spray the above anti-fouling porcelain glaze onto the surface of the ceramic tile body. The thickness of the sprayed glaze is 0.6 mm, and then sintering is carried out. The sintering temperature is 1300 °C, and the sintering time is 10 h to obtain an anti-fouling porcelain product.
[0037] Example 2
[0038] A preparation method of an anti-fouling porcelain glaze includes the following steps:
[0039] 1) After microwave treatment of the granite blocks, heat them, add carbon black and keep them warm, cool to room temperature, add an acidic reagent and crush them to obtain mixed materials. Among them, the conditions of the microwave treatment are a microwave power of 6.1 kW and a microwave treatment time of 5.2 min; the conditions of the heating are heating to 1450 °C; the mass ratio of the granite blocks to the carbon black is 5:0.29; the conditions of the heat preservation are under a pressure of 0.04 pa and a heat preservation time of 33 min; the mass ratio of the granite blocks to the acidic reagent is 30:1.4; the acidic reagent is a 6.6 mol / L aqueous citric acid solution;
[0040] 2) Add a mixing base material, deionized water, and aluminum balls to the mixed materials and perform ball milling. After sieving, an anti-fouling porcelain glaze is obtained. Among them, the mass ratio of the mixed materials to the mixing base material is 1:0.85. The mixing base material is composed of potassium feldspar, sodium feldspar, quartz, zinc oxide, calcite, dolomite, wollastonite, calcined alumina powder, Hunan kaolin, zirconium silicate, 809 frit, burnt talc, terbium oxide, dysprosium oxide, barium carbonate, and sodium carboxymethylcellulose in a mass ratio of 16.5:7.5:29:3.5:7.5:3.5:12.5:3.5:5.8:9.5:3:3.5:0.13:0.085:1.0:0.23. The weight ratio of deionized water:mixed materials and mixing base material:aluminum balls is 3:2:1. The sieving is through a 130-mesh sieve.
[0041] The granite blocks are taken from the cut-off corners of granite and consist of SiO 2 , Al 2 O 3 , Fe 2 O 3 , CaO, MgO, K 2 0, Na 2 O and TiO 2 composed in a mass ratio of 66.46:14.00:6.67:0.98:4.12:2.91:4.01:0.85.
[0042] Spray the above anti-fouling porcelain glaze onto the surface of the ceramic tile body. The thickness of the sprayed glaze is 0.6 mm, and then sintering is carried out. The sintering temperature is 1300 °C, and the sintering time is 10 h to obtain an anti-fouling porcelain product.
[0043] Example 3
[0044] A preparation method of an anti-fouling porcelain glaze includes the following steps:
[0045] 1) After microwave treatment of the granite blocks, heat them, add carbon black and then keep them warm, cool to room temperature, add an acidic reagent and perform pulverization to obtain mixed materials. Among them, the conditions of the microwave treatment are a microwave power of 6.4 kW and a microwave treatment time of 5.5 min. The conditions of the heating are heating to 1500 °C. The mass ratio of the granite blocks to carbon black is 5:0.30. The conditions of the heat preservation are a pressure of 0.08 pa and a heat preservation time of 40 min. The mass ratio of the granite blocks to the acidic reagent is 30:1.4. The acidic reagent is a 7.5 mol / L aqueous citric acid solution.
[0046] 2) Add a mixing base material, deionized water, and aluminum balls to the mixed materials and perform ball milling. After sieving, an anti-fouling porcelain glaze is obtained. Among them, the mass ratio of the mixed materials to the mixing base material is 1:0.8 - 1.0; the mixing base material is composed of potassium feldspar, sodium feldspar, quartz, zinc oxide, calcite, dolomite, wollastonite, calcined alumina powder, Hunan kaolin, zirconium silicate, 809 frit, burnt talc, terbium oxide, dysprosium oxide, barium carbonate, and sodium carboxymethylcellulose in a mass ratio of 17:8:30:4.5:8:4:13:4.5:7:10.5:4:4:0.18:0.09:2.2:0.28; the weight ratio of deionized water: mixed materials and mixing base material: aluminum balls is 3:2:1; the sieving is through a 130-mesh sieve.
[0047] The granite blocks are taken from the cut-off corners of granite and consist of SiO 2 , Al 2 O 3 , Fe 2 O 3 , CaO, MgO, K 2 0, Na 2 O and TiO 2 composed in a mass ratio of 66.46:14.00:6.67:0.98:4.12:2.91:4.01:0.85.
[0048] Spray the above anti-fouling porcelain glaze onto the surface of the ceramic tile body. The thickness of the sprayed glaze is 0.6 mm, and then sintering is carried out. The sintering temperature is 1300 °C, and the sintering time is 10 h to obtain an anti-fouling porcelain product.
[0049] Example 4
[0050] A preparation method of an anti-fouling porcelain glaze includes the following steps:
[0051] 1) After microwave treatment of the granite blocks, heat them, add carbon black and then keep them warm, cool to room temperature, add an acidic reagent and pulverize to obtain mixed materials. Among them, the conditions of the microwave treatment are a microwave power of 6.5 kW and a microwave treatment time of 6 min; the conditions of the heating are heating to 1600 °C; the mass ratio of the granite blocks to carbon black is 5:0.32; the conditions of the heat preservation are under a pressure of 0.1 Pa and a heat preservation time of 45 min; the mass ratio of the granite blocks to the acidic reagent is 30:1.5; the acidic reagent is an 8 mol / L aqueous citric acid solution.
[0052] 2) Add a mixing base material, deionized water, and aluminum balls to the mixed materials and perform ball milling. After sieving, an anti-fouling porcelain glaze is obtained. Among them, the mass ratio of the mixed materials to the mixing base material is 1:1.0. The mixing base material is composed of potassium feldspar, sodium feldspar, quartz, zinc oxide, calcite, dolomite, wollastonite, calcined alumina powder, Hunan kaolin, zirconium silicate, 809 frit, burnt talc, terbium oxide, dysprosium oxide, barium carbonate, and sodium carboxymethyl cellulose in a mass ratio of 18:9:30.5:5:9:5:14:5:8:11:5:5:0.2:0.10:2.5:0.3. The weight ratio of deionized water:mixed materials and mixing base material:aluminum balls is 3:2:1. The sieving is through a 130-mesh sieve.
[0053] The granite blocks are taken from the cut-off corners of granite and consist of SiO 2 、Al 2 O 3 、Fe 2 O 3 、CaO, MgO, K 2 0, Na 2 O and TiO 2 composed in a mass ratio of 66.46:14.00:6.67:0.98:4.12:2.91:4.01:0.85.
[0054] Spray the above anti-fouling porcelain glaze onto the surface of the ceramic tile body. The thickness of the sprayed glaze is 0.6 mm, and then sintering is carried out. The sintering temperature is 1300 °C, and the sintering time is 10 h to obtain an anti-fouling porcelain product.
[0055] Example 5
[0056] Compared with Example 2, the difference is that the microwave treatment conditions are a microwave power of 6.1 kW and a microwave treatment time of 6 min, and the other components, preparation steps, and parameters are the same.
[0057] Example 6
[0058] Compared with Example 2, the difference is that the mass ratio of granite blocks to carbon black is 5:0.32, and the other components, preparation steps, and parameters are the same.
[0059] Example 7
[0060] Compared with Example 2, the difference is that the mass ratio of granite blocks to the acidic reagent is 30:1.5, and the other components, preparation steps, and parameters are the same.
[0061] Examples 8 - 11
[0062] Compared with Example 2, the difference lies in that the dosage ratios of zinc oxide, calcined alumina powder, terbium oxide, dysprosium oxide and barium carbonate are as shown in Table 1, and the other components, preparation steps and parameters are the same.
[0063] Table 1
[0064]
[0065]
[0066] Comparative Example 1
[0067] Compared with Example 2, the difference lies in that in step 1) of Comparative Example 1, microwave treatment is not carried out, and the other components, preparation steps and parameters are the same.
[0068] Comparative Example 2
[0069] Compared with Example 2, the difference lies in that in step 1) of Comparative Example 2, carbon black is not added, and the other components, preparation steps and parameters are the same.
[0070] Comparative Example 3
[0071] Compared with Example 2, the difference lies in that in step 1) of Comparative Example 3, the mass ratio of granite blocks to carbon black is 5:0.1, and the other components, preparation steps and parameters are the same.
[0072] Comparative Example 4
[0073] Compared with Example 2, the difference lies in that in step 1) of Comparative Example 4, an acidic reagent is not added, and the other components, preparation steps and parameters are the same.
[0074] Comparative Example 5
[0075] Compared with Example 2, the difference lies in that in step 1) of Comparative Example 5, an equal amount of deionized water is added to replace the acidic reagent, and the other components, preparation steps and parameters are the same.
[0076] Comparative Examples 6 - 10
[0077] Compared with Example 2, the difference lies in that the dosage ratios of zinc oxide, calcined alumina powder, terbium oxide, dysprosium oxide and barium carbonate are as shown in Table 2, and the other components, preparation steps and parameters are the same.
[0078] Table 2
[0079]
[0080]
[0081] 1. Test the grinding times of step 1) of Examples 1 - 7 and Comparative Examples 1 - 5 respectively;
[0082] When the granite powder with a particle diameter of 10 mm or less accounts for 95 wt% of the total crushed product, stop crushing and obtain the time for crushing. The test results are shown in Table 3.
[0083] Table 3
[0084] Crushing time (h) Example 1 2.9 Example 2 2.8 Example 3 3.0 Example 4 2.9 Example 5 2.6 Example 6 2.6 Example 7 2.7 Comparative Example 1 6.6 Comparative Example 2 5.4 Comparative Example 3 4.7 Comparative Example 4 5.0 Comparative Example 5 5.2
[0085] It can be seen from the test results in Table 3 that after the microwave treatment of the present invention, carbon black is added at high temperature, and the carbon black penetrates into the interior of the granite block, increasing the total carbon content of the granite block. Combining with the addition of an acidic reagent can reduce the strength of the granite block, achieving the effect of easy crushing, greatly improving the crushing efficiency of the granite block adopting the solution of the present invention, effectively prolonging the service life of the crushing equipment, reducing energy consumption, saving costs, and meeting the requirements of environmental protection and energy conservation.
[0086] The following anti-fouling ability tests and glaze surface quality tests are respectively carried out on the anti-fouling porcelain products prepared in Examples 1-4, Examples 8-11, and Comparative Examples 4-10.
[0087] 2. Test of anti-fouling ability:
[0088] Wipe the surface of the product or test piece clean with a clean soft cloth, drop 5 drops of ink on the surface of 100 cm 2 , then wear a rubber glove on the right hand, clench the fingers, smear the ink evenly and grind it repeatedly with force. After 3 minutes, rinse the ink on its surface with water, and observe the amount of black stains adsorbed on the glaze layer surface. The amount of dirt adsorbed by the glaze is characterized by the number of black stains adsorbed on the glaze surface. The more the number of black stains, the more dirt is adsorbed. Among them, when the number of black stains is within 5, it is excellent; when it is 5-10, it is good; when it is 10-20, it is average; when it is 20-50, it is poor. The test results are shown in Table 4.
[0089] 3. Test of glaze surface quality:
[0090] Place the product on the detection table equipped with a strong incandescent lamp, and use the reflection of strong light to observe whether there are defects such as pinholes, pores, unevenness, and small brown eyes on the surface of the product. The detection method for the flatness of the glaze surface is to look at the glaze surface at eye level and visually observe whether there are obvious ripples and unevenness on the glaze surface. The test results are shown in Table 4.
[0091] Table 4
[0092] Anti-fouling ability (number of dirt points) Glaze quality Example 1 4 Good glaze effect, no defects Example 2 3 Good glaze effect, no defects Example 3 4 Good glaze effect, no defects Example 4 4 Good glaze effect, no defects Example 8 2 Good glaze effect, no defects Example 9 2 Good glaze effect, no defects Example 10 2 Good glaze effect, no defects Example 11 2 Good glaze effect, no defects Comparative Example 4 7 Good glaze effect, no defects Comparative Example 5 5 Good glaze effect, no defects Comparative Example 6 14 Glaze uneven, with pinholes Comparative Example 7 12 Glaze shrinking phenomenon appears, with air holes Comparative Example 8 13 Glaze shrinking phenomenon appears, with air holes Comparative Example 9 11 Glaze shrinking phenomenon appears, with air holes Comparative Example 10 19 Poor glaze effect, many defects
[0093] As can be seen from the test results in Table 4, compared with Comparative Examples 4-10, the anti-fouling porcelain products obtained after firing in Examples 1-4 and Examples 8-11 have good anti-fouling ability, with the number of black stains <5, belonging to the excellent level, and their anti-fouling ability is significantly better than that of Comparative Examples 4-10.
[0094] The above are only the preferred embodiments of the present invention, and do not impose any formal limitations on the present invention. Although the present invention has been disclosed above with preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some changes or modifications to equivalent embodiments by using the disclosed technical content within the scope of the technical solution of the present invention. However, as long as it does not depart from the content of the technical solution of the present invention, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a glaze for anti-fouling porcelain products, characterized in that: The preparation method comprises the following steps: 1) heating the granite block after microwave treatment, adding carbon black and keeping the temperature, cooling to room temperature, adding an acidic reagent and crushing to obtain a mixed material; 2) Adding mixed base material, deionized water and aluminum balls to the mixed material for ball milling, and then sieving to obtain anti-fouling porcelain product glaze.
2. The method for preparing a glaze for anti-fouling porcelain products according to claim 1, characterized in that: The microwave treatment conditions are as follows: microwave power of 6.0-6.5 kW and microwave treatment for 5-6 min.
3. The method for preparing a glaze for anti-fouling porcelain products according to claim 1, characterized in that: The heating condition is heating to 1400-1600°C.
4. The method for preparing a glaze for anti-fouling porcelain products according to claim 1, characterized in that: The mass ratio of the granite block to the carbon black is 5:0.28-0.
32.
5. The method for preparing a glaze for anti-fouling porcelain products according to claim 1, characterized in that: The insulation condition is to keep the temperature at a pressure of 0.01-0.1 Pa for 30-45 minutes.
6. The method for preparing a glaze for anti-fouling porcelain products according to claim 1, characterized in that: The mass ratio of the granite block to the acidic reagent is 30:1.3-1.5; the acidic reagent is a 6.5-8 mol / L citric acid aqueous solution.
7. The method for preparing a stain-resistant porcelain glaze according to claim 1, characterized in that: The mass ratio of the mixed material to the mixed base material is 1:0.8-1.
0.
8. The method for preparing a stain-resistant porcelain glaze according to claim 1, characterized in that: The mixed base material is prepared by mixing potassium feldspar, sodium feldspar, quartz, zinc oxide, calcite, dolomite, wollastonite, calcined alumina powder, Hunan kaolin, zirconium silicate, 809 frit, calcined talc, terbium oxide, dysprosium oxide, barium carbonate and sodium carboxymethyl cellulose in a mass ratio of 16-18:7-9:28.5-30.5:3-5:7-9:2.5-5:12-14:3-5:5-8:9-11:2-5:2.5-5:0.1-0.2:0.08-0.10:0.5-2.5:0.2-0.
3.
9. The method for preparing a stain-resistant porcelain glaze according to claim 1, characterized in that: The weight ratio of the deionized water: the mixed material and the mixed base material: the aluminum ball is 3:2:1; and the screening is through a 130-mesh sieve.
10. A glaze for anti-fouling porcelain products prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Ceramic containing Si-C60 and preparation method of ceramic
CN106927853A
Ceramic tile with antifouling glaze
CN107324656A
Rare earth daily ceramic glaze and method using rare earth daily ceramic glaze to prepare daily ceramic
CN108083646A
Preparation process of anti-fouling glaze for ceramic product coating
CN115231949A
Super wear-resistant marble tile and preparation method thereof
CN118894718A